Dividing Ireland : World War 1 and partition - Hennessey, Thomas (Routledge, 1998)
This text aims to provide an assessment of the First World War in Ireland and its consequences, arguing that this is the key to understanding the complexities of the Irish nation today. The author explores how the War transformed the nature of the Irish and Ulster.